2019
DOI: 10.1080/14767058.2019.1593959
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia recognised in early pregnancy is phenotypically type 2 diabetes mellitus not gestational diabetes mellitus: a case control study

Abstract: Background and aims: Gestational diabetes is defined as 'carbohydrate intolerance first recognised in pregnancy'. The definition encompasses women diagnosed in early pregnancy. Concerns exist that such cases phenotypically resemble those with established pre-existing diabetes and therefore have a higher risk profile. We aim to evaluate women diagnosed with impaired carbohydrate intolerance in early pregnancy and compare them with those with established Type 2 diabetes and gestational diabetes diagnosed on rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Overt hyperglycemia (eDiP) was associated with more severe insulin resistance, and a higher prevalence of atherogenic traits in women of an age and BMI similar to those noted in patients with mild hyperglycemia (eGDM). This observation suggests that women with eDiP present an early phenotype of type 2 diabetes rather than type 1, or MODY, which remains in line with data presented by other authors [ 36 , 37 , 38 ]. Interestingly, although women with eDiP differed from those with eGDM with respect to insulin resistance and glucose metabolism, both subgroups had a similar proportion of women with chronic and gestational hypertension.…”
Section: Discussionsupporting
confidence: 92%
“…Overt hyperglycemia (eDiP) was associated with more severe insulin resistance, and a higher prevalence of atherogenic traits in women of an age and BMI similar to those noted in patients with mild hyperglycemia (eGDM). This observation suggests that women with eDiP present an early phenotype of type 2 diabetes rather than type 1, or MODY, which remains in line with data presented by other authors [ 36 , 37 , 38 ]. Interestingly, although women with eDiP differed from those with eGDM with respect to insulin resistance and glucose metabolism, both subgroups had a similar proportion of women with chronic and gestational hypertension.…”
Section: Discussionsupporting
confidence: 92%
“…The most of the studies published in literature in order to better define the physiophatological mean of overt type 2 diabetes compare this pathology to GDM. In a case control study Agha-Jaffar et all showed an higher frequency of hypertensive disorders and an higher frequency on insulin treatment in OT2DM compared to GDM ones and pointed the fact that OT2DM is phenotypically a type 2 diabetes mellitus (13). In a multi-ethnic cohort in Spain pregnant women with OT2DM showed worse obstetric outcomes with respect to GDM ones and this was present mainly in women from ethnic minorities ( 14).…”
Section: Discussionmentioning
confidence: 93%
“…Most studies are published in the literature in order to better define the physiopathological mean of overt diabetes compared to GDM pathology [11][12][13][14]. In a case-control study, Agha-Jaffar et al reported a higher frequency of hypertensive disorders and higher frequencies with respect to insulin treatment in ODM compared to women with GDM, and pointed out the fact that ODM is phenotypically a type 2 diabetes mellitus [22]. In a multi-ethnic cohort in Spain, pregnant women with ODM exhibited worse obstetric outcomes with respect to women with GDM, and this was present mainly in women from ethnic minorities [23].…”
Section: Discussionmentioning
confidence: 99%